The relationship of aerobic endurance and linear speed on repeat sprint ability performance in female international footballers - Doyle, B.; Browne, D.; Horan, D. (International Journal of Human Movement and Sports Sciences, 2020)
The aim of this study was to investigate the relationship between aerobic endurance and linear speed on repeat sprint ability performance in female international footballers. Twenty-five female international football players completed 10-m, 20-m, 30-m linear speed, repeat sprint ability (RSA) and yo-yo intermittent recovery, level 1 tests. Pearson's product correlation (r) was used to assess the relationship between 10-m, 20-m and 30-m sprint times (S10-m, S20-m, S30-m) sprint time on the first trial of the repeated sprint test (RST1) and yo - yo intermittent recovery test, level 1 (YYIR1) with total repeated sprint time (RSTT). Linear regressions were used to describe the relationship between the dependent variable (RSTT) and independent variables (S10-m, S20-m, S30-m, RST1 and YYIR1). Pearson's correlation analysis indicated a large negative correlation between RSTT and YYIR1 performance (r = -0.58, P = .002), a very large significant relationship was established between S10-m and S20-m whilst an almost perfect relationship was present for S30-m and RST1. The results of the linear regression proved the independent variable RST1 explained 85% (adjusted R2) of the variation in RSTT scores. S10-m, S20-m and S30-m performance accounted for 62 - 83% of the variation in RSTT scores whilst YYIR1 performance only accounted for 33.6%. The results of this study indicate that fast linear speed can positively impact on RSTT performance whilst reduced aerobic endurance capabilities may negatively influence RSTT performance in female international footballers.